Imbalances in Copper or Zinc Concentrations Trigger Further Trace Metal Dyshomeostasis in Amyloid-Beta Producing Caenorhabditis elegans - Metaxas, Ada (Frontiers in Neuroscience, 2021)
Alzheimer's Disease (AD), a progressive neurodegenerative disease characterized by the buildup of amyloid-beta (Aβ) plaques, is believed to be a disease of trace metal dyshomeostasis. Amyloid-beta is known to bind with high affinity to trace metals copper and zinc. This binding is believed to cause a conformational change in Aβ, transforming Aβ into a configuration more amenable to forming aggregations. Currently, the impact of Aβ-trace metal binding on trace metal homeostasis and the role of trace metals copper and zinc as deleterious or beneficial in AD remain elusive. Given that Alzheimer’s Disease is the sixth leading cause of adult death in the U.S., elucidating the molecular interactions that characterize Alzheimer’s Disease pathogenesis will allow for better treatment options. To that end, the model organism C. elegans is used in this study. C. elegans, a transparent nematode whose connectome has been fully established, is an amenable model to study AD phenomena using a multi-layered, interconnected approach. Aβ-producing and non-Aβ-producing C. elegans were individually supplemented with copper and zinc. On day 6 and day 9 after synchronization, the percent of worms paralyzed, concentration of copper, and concentration of zinc were measured in both groups of worms. This study demonstrates that dyshomeostasis of trace metals copper or zinc triggers further trace metal dyshomeostasis in Aβ-producing worms, while dyshomeostasis of copper or zinc triggers a return to homeostasis in non-Aβ-producing worms. This supports the characterization of Alzheimer’s Disease as a disease of trace metal dyshomeostasis.